A Quantitative Attribute Analysis of the Ubaid-Period Ceramic Corpus from Kenan Tepe - Parker, Bradley J. (Bulletin of ASOR, 2010)
Research on Ubaid ceramics has traditionally focused on categorizing and describing ceramic types or building chronologies. Only in a few cases have researchers sought a broader understanding of Ubaid assemblages by focusing on the quantification, rather than the qualification, of Ubaid ceramic data. In this study, we analyze the entirety of the Ubaid ceramic assemblage from reliable contexts at the site of Kenan Tepe in southeastern Turkey—a total of 14,333 ceramic sherds. In sorting the ceramics by fabric, form, surface treatment, rim type, and vessel size, this study provides statistically significant empirical data pertaining to three avenues of analysis. First, we focus on the characteristics of the overall assemblage of Ubaid ceramics from Kenan Tepe. Second, we analyze the data diachronically to highlight stability and change through the four phases of Ubaid occupation at Kenan Tepe. And third, we investigate the spatial distribution of part of the assemblage in and around a large Ubaid-period domestic structure. We contend that quantitative studies of entire excavated ceramic assemblages allow researchers a more complete understanding of ceramic assemblages, provide a firmer foundation for theorizing vessel function, and offer the tools to make empirically based assessments of ancient lifeways.